2015
DOI: 10.3382/ps/pev013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed supplemented with fermented pine needles (Pinus ponderosa) on growth performance and antioxidant status in broilers

Abstract: The objective of this study was to compare the effects of Aspergillus niger-fermented pine needles and nonfermented pine needles on growth performance and antioxidant capacity in broiler chicks. In total, 300 1-day-old broiler chicks were randomly allocated to 5 dietary treatments, which were then denoted as the control treatment (basal diet); the nonfermented treatment (containing 0.3% and 0.6% nonfermented treatment, respectively, in the starter and grower phase); or the fermented 1, fermented 2, or fermente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 24 publications
4
19
0
2
Order By: Relevance
“…The relatively same densities that also shows no difference of THI on each pen is suspected as a factor for the exceed-free radical absence, meaning that heat stress in each pen showed no oxidative stress. This is in accordance with Wu et al, (2015) which shows the no effect of liver malondialdehyde level of 21-days and 42-days control treatment broiler maintained with stocking density of 8 birds m -2 . In case of heat stress among treatment cage density may affect the levels of malondialdehyde due to an increase in oxidative stress.…”
Section: Stress Indicatorssupporting
confidence: 91%
“…The relatively same densities that also shows no difference of THI on each pen is suspected as a factor for the exceed-free radical absence, meaning that heat stress in each pen showed no oxidative stress. This is in accordance with Wu et al, (2015) which shows the no effect of liver malondialdehyde level of 21-days and 42-days control treatment broiler maintained with stocking density of 8 birds m -2 . In case of heat stress among treatment cage density may affect the levels of malondialdehyde due to an increase in oxidative stress.…”
Section: Stress Indicatorssupporting
confidence: 91%
“…Levels of serum catalase (CAT), glutathione superoxide dismutase (GSH-Px), malondialdehyde (MDA), superoxide dismutase (SOD), and antioxidant capacity (AOC) were analyzed by spectrophotometrical methods with ELISA assay kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China) according to the manufacturer’s instructions. These antioxidant enzymes play an important role in balancing redox status (Wu et al 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, fermented herbs, including Ginkgo biloba leaves, Pinus needles, reportedly improve growth performance, feed efficiency, meat quality, immune function, and blood parameters in livestock (Ahmed et al 2016 ; Wu et al 2015 ; Zhang et al 2015 ). Fermented herbs such as Anoectochilus formosanus Hyata, Flos Lonicera , and Rhizoma Atractylodis Macrocephalae have antioxidant activity and modulate the intestinal microbiota of rats (Ng et al 2011 ; Wang et al 2014a , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kim, Kim, Choi, et al (2012a) reported after the supplementation of mixture of pine leaves powder and mugwort in boiler, a significant decrease in LDL and total cholesterol was seen. Similarly, Wu, Wang, Wang, Li, and Qi (2015) reported the effects of pine leaves extracts and found significant decreases in total cholesterol in rats. It is assumed from the study that pine leaves play an important role in the reduction of lipids which may be due to the presence of lipid lower potent biochemical substances (Kim, Kim, Min, et al, 2012b).…”
Section: Discussionmentioning
confidence: 93%